The Trial That Never Ends : Hannah Arendt's 'Eichmann in Jerusalem' in Retrospect - Golsan, Richard J. (Book collections on Project MUSE., 2017)
The contributors gathered together by Richard J. Golsan and Sarah M. Misemer in The Trial That Never Ends assess the contested legacy of Hannah Arendt's famous book and the issues she raised.